2021
DOI: 10.1096/fj.201903192rr
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte‐like cells undergo transcriptional reprogramming and distinct functional adaptations in acute lung injury

Abstract: We previously reported on the role of pericyte-like cells as functional sentinel immune cells in lung injury. However, much about the biological role of pericytes in lung injury remains unknown. Lung pericyte-like cells are well-positioned to sense disruption to the epithelial barrier and coordinate local inflammatory responses due to their anatomic niche within the alveoli. In this report, we characterized transcriptional responses and functional changes in pericyte-like cells following activation by alveolar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
(79 reference statements)
2
8
0
Order By: Relevance
“…Potential mechanisms include directed trafficking of leukocytes across the interstitium via matrix remodeling and upregulation of leukocyte adhesion molecules, similar to what had been shown in cremaster muscle ( 22 ), and upregulation of chemokines ( 23 ). Indeed, we have previously demonstrated that lung pericyte-like cells upregulate proinflammatory processes similar to what has been shown in other organs, including adhesion molecules (e.g., VCAM and ICAM) and cytokines/chemokines (e.g., MCP-1, CXCL1, and IL-6) ( 10 , 11 ). Although the regulation of lung inflammation is beyond the scope of this report, these findings collectively support further investigation into the novel mechanisms by which pericytes direct leukocyte response in the lung.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Potential mechanisms include directed trafficking of leukocytes across the interstitium via matrix remodeling and upregulation of leukocyte adhesion molecules, similar to what had been shown in cremaster muscle ( 22 ), and upregulation of chemokines ( 23 ). Indeed, we have previously demonstrated that lung pericyte-like cells upregulate proinflammatory processes similar to what has been shown in other organs, including adhesion molecules (e.g., VCAM and ICAM) and cytokines/chemokines (e.g., MCP-1, CXCL1, and IL-6) ( 10 , 11 ). Although the regulation of lung inflammation is beyond the scope of this report, these findings collectively support further investigation into the novel mechanisms by which pericytes direct leukocyte response in the lung.…”
Section: Discussionsupporting
confidence: 61%
“…They are critical in the development of vasculature during embryonic development and play a role in maintaining endothelial integrity during homeostasis in a number of organs ( 9 ). Recent work by our group demonstrated a role for pericytes as immune regulators in the lung ( 10 , 11 ). The role of pericytes in lung fibrosis remains a much-debated issue.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that primary mouse lung pericytes express functional TLRs 2/1, 2/6, 4, 7, 9 ( 15 ). In response to TLR agonists, lung pericytes upregulate cytokine expression, including chemokines for neutrophils, monocytes and lymphocytes, and adhesion molecule expression in vitro and in vivo ( 15 , 16 ). Furthermore, cultured mouse lung pericytes exposed to alveolar contents from uninjured and sterilely injured lungs [bronchoalveolar lavage fluid (BALF) collected from uninjured and injured mice] induced inflammatory programs in lung pericytes ( 15 ).…”
Section: Recruitment and Trafficking Of Leukocytesmentioning
confidence: 99%
“…In this review, we focus on the mechanisms by which pericytes activate local inflammatory responses after lung injury. Work from our group, using transgenic models that label mouse lung pericytes, has demonstrated robust inflammatory responses in pericytes and attenuated lung inflammation when pericytes are selectively depleted ( 14 16 , 34 ). Although this review focuses on the role of perivascular cells in lung inflammation, studies in extrapulmonary organs, such as the CNS and the heart, reveal similar biological responses to organ injury ( 35 , 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…This unique location between the epithelium and endothelium may position pericytes to transmit alveolar epithelial-derived injury signals to the endothelium and thereby play a major role in lung injury development. Indeed, recent studies in mice have identified that pericytes function as immune sensors that respond to alveolar epithelial damage by promoting inflammatory cell recruitment [ 115 , 116 , 117 , 118 ].…”
Section: Alveolar Epithelial Responses That Lead To Lung Injurymentioning
confidence: 99%